SIKAP KONSUMEN DALAM MEMBELI SAYURAN DI PASAR TRADISIONAL DAN PEDAGANG SAYUR KELILING DI KABUPATEN KOLAKA - Masitah Masitah; Nursalam Nursalam; Dewi Yulan Dari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Vegetables are one of the horticultural commodities that have high economic value, can be a source of income for the community and farmers. The need for vegetables is increasing along with the growth of the population, especially regarding consumer decisions in consuming vegetables. To find out what consumers want, it requires the support of accurate and detailed market information covering consumer behavior. This study aims to determine the characteristics and attitudes of consumers in buying vegetables at traditional markets and traveling vegetable vendors. This research was carried out from February to March 2022 in Anaiwoi Village, Tangggetada District, Kolaka Regency. The samples in this study were taken by accidental sampling and quota sampling. The sample studied was 30 respondents of housewives who shopped at traditional markets and 30 respondents of housewives who shopped at traveling vegetable vendors. The methods used in this study are qualitative descriptive analysis and multiatribute analysis of fishbein. The results showed that consumer attitudes have 4 assessment attributes, namely the price of vegetables, the freshness of vegetables, the cleanliness of vegetables and the diversity of vegetables. from the results of the multiatribute analysis of fishbein explained that the highest attitude value of vegetables in traditional markets is found in the attributes of vegetable diversity and vegetable freshness. Meanwhile, the highest attitude value of vegetables in traveling vegetable vendors is in the attributes of vegetable hygiene. The neutral attitude is on the attributes of freshness and diversity of vegetables.